A non‐canonical function of Ezh2 preserves immune homeostasis. (21st February 2017) - Vasanthakumar, Ajithkumar; Xu, Dakang; Lun, Aaron TL; Kueh, Andrew J; van Gisbergen, Klaas PJM; Iannarella, Nadia; Li, Xiaofang; Yu, Liang; Wang, Die; Williams, Bryan RG; Lee, Stanley CW; Majewski, Ian J; et al.
Abstract: Enhancer of zeste 2 (Ezh2) mainly methylates lysine 27 of histone‐H3 (H3K27me3) as part of the polycomb repressive complex 2 (PRC2) together with Suz12 and Eed. However, Ezh2 can also modify non‐histone substrates, although it is unclear whether this mechanism has a role during development. Here, we present evidence for a chromatin‐independent role of Ezh2 during T‐cell development and immune homeostasis. T‐cell‐specific depletion of Ezh2 induces a pronounced expansion of natural killer T (NKT) cells, although Ezh2‐deficient T cells maintain normal levels of H3K27me3. In contrast, removal of Suz12 or Eed destabilizes canonical PRC2 function and ablates NKT cell development completely. We further show that Ezh2 directly methylates the NKT cell lineage defining transcription factor PLZF, leading to its ubiquitination and subsequent degradation. Sustained PLZF expression in Ezh2‐deficient mice is associated with the expansion of a subset of NKT cells that cause immune perturbation. Taken together, we have identified a chromatin‐independent function of Ezh2 that impacts on the development of the immune system. Synopsis: Increasing evidence indicates that the histone methyltransferase Ezh2 also modifies non‐histone substrates in a chromatin‐independent fashion. This study shows that Ezh2 controls immune homeostasis through such a non‐canonical mechanism by directly methylating the transcription factor PLZF. Loss of Ezh2 leads to the accumulation of PLZF high NKT cells, whereas the depletion of Eed and Suz12 blocks NKT cell development. PLZF in the expanded Ezh2‐depleted NKT cell population shows increased protein stability. Ezh2‐dependent methylation of PLZF creates a "methyl degron", which promotes the ubiquitinylation and degradation of PLZF. Ezh2‐deficient PLZF high NKT cells perturb the homeostasis of T cells and B cells. Abstract : Increasing evidence indicates that the histone methyltransferase Ezh2 also modifies non‐histone substrates in a chromatin‐independent fashion. This study shows that Ezh2 controls immune homeostasis through such a non‐canonical mechanism by directly methylating the transcription factor PLZF.